Hygiene practices in slaughterhouses and public health risk: A scoping review - Mohammad Abdus Shahid Hossain; Nelima Ibrahim; Karen N. Barnett (PLoS ONE, 2025)
Introduction Slaughterhouses are facilities where animals are slaughtered for meat production. Poor hygiene practices in these facilities, especially in developing countries, pose significant public health risks. The lack of regulation and substandard conditions can lead to the transmission of diseases from animals to humans, particularly affecting slaughterhouse workers who are in close contact with animals and animal products. A scoping review was conducted to map and summarize existing evidence on hygiene practices in slaughterhouses and evaluate their effectiveness in mitigating public health risks. Methodology This review used the Joanna Briggs Institute Collaboration (JBI) scoping review inclusion framework Population Concept and Context (PCC) and PRISMA for Scoping Review (PRISMA-ScR) guidelines. Databases searched included; EBSCO Medline, Web of Science, EMBASE, and grey literature from BASE and Google Scholar. The studies were screened for eligibility and data extracted from included studies using the JBI data extraction chart. Included studies were assessed for risk of bias using cross-sectional and prevalence studies quality assessment tools. Results Fourteen studies were included published between January 2002 and May 2023. These studies were conducted in 10 countries, with one-third (n = 5) originating from Nigeria. Twelve studies used cross-sectional surveys, while one employed a prevalence survey. This review identified common hygiene practices relating to personal hygiene [handwashing with soap and water] and environmental hygiene (cleaning tools and surfaces). Overall, workers’ reported that they had good knowledge of hygiene practices; handwashing (95.7%), using protective apparatus (89.7%), and cleaning equipment (89.3%). Studies reported that over half of slaughterhouse workers wore protective clothing. However, much less (12%) reported that they cleaned their knives before and after use, and it was reported that some slaughterhouses disposed of refuse improperly (bush], raising important public health concerns. Only three studies clearly linked slaughterhouse hygiene practices with public health risks. Conclusion Improving hygiene practices in slaughterhouses is crucial for reducing public health risks. Gaps in knowledge, inadequate training, insufficient inspections and poor infrastructure were identified as key areas for improved guidelines and policy intervention.